AB0686 Cross Sectional Cohort of Inflammatory Bowel Disease Related Arthritis in Rheumatology Secondary Care. (15th July 2016) - Morrison, H.D.; Sengupta, R.; Tillett, W.
Abstract : Background: Joint involvement associated with inflammatory bowel disease (IBD) is well recognised within the concept of spondyloarthritis (SpA). There are two groups of articular manifestation in IBD: an axial arthropathy, including inflammatory back pain, sacroiliitis and ankylosing spondylitis (AS); and a lesser-studied peripheral arthritis, which is broadly divided into type 1 (oligoarthritis) and type 2 (polyarthritis). Previous data comes largely from cohorts of patients studied in gastroenterology secondary care, and identifies IBD related arthritis as a common and poorly understood condition. Objectives: To describe the demographic characteristics, clinical features and current assessment and treatment of patients with Crohn's Disease (CD) or Ulcerative Colitis (UC) related arthritis in rheumatology secondary care. Methods: One hundred consecutive patients with a physician diagnosis of IBD related arthritis were selected for inclusion. Data was collected retrospectively from patient notes, hospital electronic records and imaging software. Demographic, patient reported, clinical and treatment data was collected. Results: In this group of 100 patients, mean age 48.8 years (range 22–86), mean disease duration 7.8 years was an equal proportion of men (54) and women (46) and IBD subtype (CD=53, UC=41, Indeterminate=5, other=3). Disease phenotype and radiographic damage are described in table 1 . At the last clinic assessment only 36% of patients had a tender and swollen joint count documented. The burden of peripheral symptoms was small with an average tender joint count of 1.43 (range 0–12) and swollen joint count of 0.67 (range 0–14). Frequency of axial and peripheral symptom assessment was similar at 72% and 75% respectively. Gut symptoms were only assessed in 50% of patients. 21% of patients had a documented history of uveitis and 22% a history of enthesitis. In patients with axial symptoms the mean outcome measures were as follows: BASDAI =4.4 (range 0.9–7.1), BASMI =3.7 (range 0–7.4) BASFI =4 (range 0–8.6), back pain =4 (range 0–9), patient global assessment =3.3 (range 1–9). 79% of patients had a current or prior treatment history with one or more disease modifying anti rheumatic drugs (DMARD), and 37% with anti-TNF therapy. At least 11% had a history of non-steroidal anti-inflammatory use. Conclusions: We report data describing a distinct but heterogeneous clinical phenotype of IBD associated arthritis in rheumatology secondary care. We found high rates of DMARD and anti-TNF use, little erosive peripheral disease and variable clinical assessment. We suggest there is a need for improved assessment of IBD associated arthritis to better quantify the burden of disease and natural history. Disclosure of Interest: None declared